The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1111/j.1460-2466.2006.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Negativity and Motivated Information Processing During a Political Campaign

Abstract: This research investigated how voters select, process, are affected by, and recall political information in a dynamic campaign environment. It was hypothesized that voters' information selection, processing, and recall are subject to a negativity bias (i.e., negative information dominates over positive information), a congruency bias (i.e., positive information about the preferred candidate and negative information about the opponent candidate dominate over negative information about the preferred candidate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
181
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(197 citation statements)
references
References 64 publications
10
181
2
4
Order By: Relevance
“…6 Meffert et al (2006) find a very similar result in another simulated campaign experiment. 7 We report evidence of this phenomenon below in the Study 2 experiment concerning the belief that Iraq had weapons of mass destruction immediately before the U.S. invasion.…”
Section: Theoretical Expectationssupporting
confidence: 84%
“…6 Meffert et al (2006) find a very similar result in another simulated campaign experiment. 7 We report evidence of this phenomenon below in the Study 2 experiment concerning the belief that Iraq had weapons of mass destruction immediately before the U.S. invasion.…”
Section: Theoretical Expectationssupporting
confidence: 84%
“…Experimental studies that have tried to determine whether people are motivated to select congenial options yield mixed support for selective exposure. In some instances, individuals do tend to choose information supporting their beliefs (Adams 1961;Barlett et al 1974;Chaffee and McLeod 1973;Donsbach 1991;Mills 1965a;Redlawsk 2002;Taber and Lodge 2006), but not always (Feather 1962;Freedman 1965;Meffert et al 2006;Mills et al 1959;Rosen 1961). These conflicting results point to the possibility of a number of contingent conditions that influence whether people engage in selective exposure to news media (Cotton 1985;Frey 1986).…”
Section: Selective Exposurementioning
confidence: 72%
“…Scholars have suggested that individuals are hardwired for negative information (24)(25)(26)(27). Research has provided strong evidence that negatively valenced information (eg, news stories with a "conflict" frame) is more likely to be selectively viewed (28)(29)(30)(31)(32).…”
Section: Selectionmentioning
confidence: 99%